Investigation of Rutting and Low Temperature Cracking Behavior of Reactive Ethylene Terpolymer and Waste Cooking Oil Modified Bitumen - Kumandas, Aytug; Cavdar, Erman; Sahan, Neslihan; Kok, Baha Viral; Pancar, Erhan Burak; Oruc, Seref (Turkish Chamber Civil Engineers, 2024)
With sustainability being the most crucial issue of recent years, the use of waste materials in bitumen modification has been increasing and becoming widespread. In this experimental study, it was aimed to investigate the high- and low-temperature behavior of bitumen samples modified with waste cooking oil (WCO), reactive ethylene terpolymer (RET), and polyphosphoric acid (PPA). Accordingly, the multiple stress creep and recovery (MSCR) test and the bending beam rheometer (BBR) test were conducted. Depending on the increasing WCO ratio, the Jnr, R%, Delta T-c, and lambda parameters of modified bitumens were examined in detail. It was observed that with increasing WCO ratio, the Jnr value increased, and elastic recovery and stiffness decreased. In addition, it was determined that this composite-modified bitumen is resistant to heavy traffic loads and has sufficient flexibility at low temperatures.
Keywords: Reactive ethylene terpolymer; waste cooking oil; bitumen modification; MSCR; BBR